CD3G or CD3D Knockdown in Mature, but Not Immature, T Lymphocytes Similarly Cripples the Human TCRαβ Complex - Garcillán, Beatriz; Fuentes, Patricia; Marin, Ana V.; Megino, Rebeca F.; Chacon-Arguedas, Daniel; Mazariegos, Marina S.; Jiménez-Reinoso, Anaïs; Muñoz-Ruiz, Miguel; Laborda, Raquel G.; Cárdenas, Paula P.; Fernández-Malavé, Edgar; Toribio, Maria L.; et al. (Frontiers in Cell and Developmental Biology, 2021)
The human αβ TCR is composed of a variable heterodimer (TCRαβ) and three invariant dimers (CD3γε, CD3δε and ζζ/CD2472). The role of each invariant chain in the stepwise interactions among TCR chains along assembly are still not fully understood. Despite the high sequence homology between CD3γ and CD3δ, the clinical consequences of the corresponding immunodeficiencies (ID) in humans are very different (mild and severe, respectively), and mouse models do not recapitulate findings in human ID. To try to understand such disparities, we stably knocked down (KD) CD3D or CD3G expression in the human Jurkat T-cell line and analyzed comparatively their impact on TCRαβ assembly, transport and surface expression. The results indicated that TCR ensembles were less stable and CD3ε levels lower when CD3γ, rather than CD3δ, was scarce. However, both defective TCR ensembles were strongly retained in the ER, lacked ζζ/CD2472 and barely reached the T-cell surface (< 11% of normal controls) in any of the CD3 KD cells. This is in sharp contrast to human CD3γ or δ ID, whose mature T cells express higher levels of surface TCR (> 30% vs normal controls). CD3 KD of human T-cell progenitors before mouse fetal thymus organ cultures showed high plasticity in emerging immature polyclonal T lymphocytes that allowed for the expression of significant TCR levels which may then signal for survival in CD3γ, but not in CD3δ deficiency, and explain the immunological and clinical disparities of such ID cases.